Paradigma Nusantara: Decolonizing Science Agenda - Aji Dedi Mulawarman (International Journal of Religious and Cultural Studies, 2021)
This research aims to propose Paradigma Nusantara as a means to redirect science to the roots of cultural and religious values that become the human characters of Nusantara. By using Hikmah philosophy, this paradigm was built with principal tenets. Modern paradigms are built with philosophical assumptions (epistemology, ontology, axiology/human nature), which reflect anthropocentric interests. Paradigma Nusantara, on the other hand, is built with four substantive tenets (kaidah substantif), namely Nusantara being, integral view of reality, religiousity and culture, and the objective of Nusantara knowledge. This paradigm, if applied into practice will be able to decolonize science, including accounting, that in the present time is still dense with Western and secular values, and will bring about creation of science that is in accordance with religions and local wisdom (culture).